Bactericidal activities of cefprozil, penicillin, cefaclor, cefixime, and loracarbef against penicillin-susceptible and -resistant Streptococcus pneumoniae in an in vitro pharmacodynamic infection model. - Cappelletty, D M (1996)
We examined the bactericidal activities of penicillin, cefprozil, cefixime, cefaclor, and loracarbef against three clinical isolates of Streptococcus pneumoniae which were susceptible, moderately susceptible, and resistant to penicillin. An in vitro two-compartment glass infection model was used to simulate human pharmacokinetics in the presence of bacteria. Also, changes in organism susceptibility and development of resistant subpopulations were evaluated. Simulated pediatric dosage regimens and target peak concentrations in the central compartment were as follows: penicillin V-potassium, 26 mg/kg of body weight every 6 h (q6h) and 14 micrograms/ml; cefaclor, 13.4 mg/kg q8h and 16 micrograms/ml; loracarbef, 15 mg/kg q12h and 19 micrograms/ml; cefprozil, 15 mg/kg q12h and 11 micrograms/ml; and cefixime, 8mg/kg q24h and 4 micrograms/ml. Targeted half-lives of each agent were 1 h for penicillin, cefaclor, and loracarbef; 1.3 h for cefprozil; and 3.5 h for cefixime. Growth controls were performed at two different pump rates, 0.8 and 2.0 ml/min (half-lives = 3.5 and 1 h, respectively). Each isolate demonstrated autolysis at the lower rate which was attributed to a decreased supply of fresh nutrients available to the organisms in the infection compartment. Against the susceptible isolate, the time to 99.9% killing was statistically significant between penicillin V-potassium and both cefaclor and cefixime (P < 0.029). Loracarbef never achieved a 99.9% reduction in the inoculum. At 48 h penicillin, cefprozil, and cefaclor were equivalent in extent of killing. Against the intermediately resistant isolate, cefprozil was superior to all other regimens with respect to rate of killing (P < 0.013) and extent of killing at 24 h (P < 0.0003). At 48 h penicillin, cefprozil, and cefaclor were equivalent in extent of killing. All of the regimens exhibited inferior activity against this penicillin-resistant isolate. A 99.9% kill was never obtained with any of the regimens, nor was there an appreciable decrease in the colony counts. In conclusion, it appears that cefprozil, penicillin, and cefaclor are effective therapies against sensitive and even intermediately sensitive isolates of S. pneumoniae. However, none of the oral therapies appear to be of any benefit against penicillin-resistant isolates. The in vitro model may be an effective tool in evaluating other multiple-dose therapies against this fastidious organism, since the continual supply of fresh medium maintains the viability of S. pneumoniae with minimal stationary-phase autolysis.